Анизотропный термоэлемент в режиме генерации эдс и тока - Anatychuk, L. I.; Prybyla, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
Computer methods for the description of the anisotropic thermoelement (AT) properties with regard to all necessary model approximations have been elaborated. Configurations of eddy thermoelectric currents in the anisotropic thermoelement caused by current contacts have been found. The properties of the AT with regard to temperature dependences of material properties, contact resistances and current contacts have been determined for concrete cases. Optimal dimensions of current contacts have been found. The optimization of AT construction allowed to increase its efficiency by 15%.